The moderating impact of security on intention to use e-money transaction in Indonesia: A conceptual framework - Husnil, Khatimah; Halim, Fairol (2014)
This research examines the moderating impact of security on intention to use e-money that adapted from variables of the TAM (Technology Acceptance Model) and TPB (Theory of Planned Behavior). This study uses security as moderating variable and finds the relationship depends on customer intention to use e-money as payment tools. The conceptual framework of e-money transactions is reviewed to understand behavioral intention of consumers from perceived usefulness, perceived ease of use, perceived behavioral control and security. Quantitative method is utilized as sources of data collection. A total of one thousand respondents are selected using quota sampling method in Medan, Indonesia. Descriptive analysis and Multiple Regression analysis are conducted to analyse the data. The article ended with suggestion for future studies.